International law of the sea - Tanaka, Yoshifumi (Cambridge, 2015)
"This new edition has been fully revised and updated to include the contemporary issues together with new cases delivered by international courts and tribunals, such as the ICJ, ITLOS and Arbitral Tribunals, treaties, UN resolutions, and other instruments. It retains the clear chapter structure of the first edition, but has expanded the topics on marine spaces beyond national jurisdiction, maritime delimitation, protection of the marine environment. A new concluding chapter has also been included and presents a perspective on the future development of the international law of the sea. Detailed footnotes and further reading sections, combined with illustrations and tables ensure understanding of the subject. By offering clarity of expression and academic rigour, The International Law of the Sea remains the best choice for students"--